EFFICACY OF SHORT TERM VIDEO EEG IN DETECTING PSYCHOGENIC NON-EPILEPTIC SEIZURES - Parameswaran, Sajeesh; Vijayamma, Anil Kumar Thankappakurup; Pillai, Ananthanarayana Marthanda (Malang Neurology Journal, 2019)
Background: Short term video Electroencephalography (SVEEG) is a non-invasive diagnostic procedure typically last for about 1-5 hours. SVEEG can be utilize to differentiate epileptic from Psychogenic Non-epileptic Seizures (PNES). Objective: To assess the yield of short term video EEG in detecting PNES.Methods: Retrospective analysis of short term video EEG in a tertiary level hospital. Patient history, provisional diagnosis, previous EEG and imaging reports were tabulated. Various short term video EEG findings like epileptiform abnormalities, PNES and other non-epileptic events were analyzed in detail. According to the provisional diagnosis formed two groups; Suspecting NEE and suspecting seizure disorders. Change in the provisional diagnosis after SVEEGs were also studied.Results: A total of 417 SVEEGs analyzed: 34(8.2%) patients developed events to suggest PNES, 16(3.8%) patients had other non-epileptic events; 96(23%) showed interictal epileptiform discharges,15 (3.6%) showed seizures and 90(21.6%) patients showed non specific EEG abnormalities. Around 60% SVEEGs were conclusive.Conclusion: A diagnostic event was recorded during SVEEG in majority of patients in the PNES group. SVEEG is a cost effective and useful diagnostic procedure; especially to identify non-epileptic events.